Hubungan Perilaku Ibu Tentang Higenitas Botol Susu Dengan Kejadian Diare Pada Bayi Usia 6 - 24 Bulan di Klinik Pratama Mariana - Pardede, Debora Yolanda Octaviani; Raja GukGuk, Siti Nelly; Bate’e, Siska Yanti Niscahaya; Toruan, Krisnawati L; Silaban, Verawaty Fitrinelda (Journal of Telenursing (JOTING), 2024)
This study aims to determine the relationship between maternal behavior regarding the hygiene of milk bottles and diarrhea in babies aged 6-24 months at the Pratama Mariana Clinic in 2023. The data collection method uses quantitative research with a cross-sectional plan. Data collection uses a questionnaire sheet. The statistical test used is chi-square. The research results showed that the results of the chi-square test obtained a p value of 0.000, meaning that there was a relationship between mothers' knowledge, attitudes and actions regarding the hygiene of milk bottles and the incidence of diarrhea in babies aged 6-24 months. In conclusion, the research results show that there is a relationship between maternal behavior regarding milk bottle hygiene and the incidence of diarrhea in babies aged 6-24 months. Keywords: Baby, Diarrhea, Milk Bottle Hygiene, Behavior